Assessing the Effectiveness of Islamic Law in Addressing Free Social Interactions: A Socio-Religious Literature Analysis in Indonesia - Pahrul, Pahrul (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2025)
Free social interaction (commonly referred to as pergaulan bebas) can be defined as deviant behavior that violates social and religious norms. More specifically, the term is often associated with sexual relationships outside the bounds of official marital commitment. The current condition of such behavior has reached an alarming level, with increasing types of misconduct, a growing number of cases, and broader demographic involvement. This phenomenon is deeply concerning, as it can lead to the breakdown of individuals, families, communities, and even human civilization as a whole. As a religion believed to offer a complete and comprehensive legal framework, Islam provides an essential perspective in addressing the issue of free social interaction. Thus, it is necessary to examine how effective Islamic law is in tackling this moral crisis. Through a library research method, it is found that pergaulan bebas is influenced by multiple factors, including individual behavior, societal norms, social media, and governmental policies. The findings also reveal that Islamic law remains relevant across all times and contexts and proves to be highly effective in both preventing and resolving issues related to free social interaction. Among the Islamic legal principles are commands to maintain piety (taqwa) and to equip oneself with religious knowledge. Islam also sets specific guidelines for social conduct, such as the obligation to lower one’s gaze, dress modestly, and avoid seclusion (khalwat) or mixed-gender interactions without clear boundaries (ikhthilath). Furthermore, Islamic law enforces explicit and firm punishments for those who violate these moral boundaries, serving both as a deterrent and a corrective mechanism. This paper aims to contribute meaningful insights that may serve as a valuable reference for policymakers in formulating strategies to combat the issue of pergaulan bebas effectively.